Development and Effectiveness Evaluation of a One-Stop Cataract Surgery Nursing Service Model for Non-admitted Patients at Chaiyaphum Hospital - Phoomsathan, Patcharachat; Jantasin, Bhanwasa; Kraphankio, Sineenart; Thongsarn, Piyathida (Journal of The Royal Thai Army Nurses, 2025)
This research aims to develop and evaluate the effectiveness of a nursing service model for same-day cataract surgery patients at Chaiyaphum Hospital. The purposive sample included 10 professional nurses, 2 ophthalmologists, 1 pharmacist, 40 cataract surgery patients, and their 40 caregivers. The research was conducted in three phases: 1) Situation analysis, 2) Model development, and 3) Evaluation of model effectiveness. The research instruments included interview, focus group, the WE Line CV model nursing service framework, knowledge tests, caregiving skill assessment forms, and satisfaction questionnaires for caregivers and professional nurses. The content validity of the instruments was verified by five experts, with reliability coefficients of .72, .75, and .84, respectively. Data were analyzed using descriptive statistics and a paired t-test. The results revealed that the WE Line CV model consisted of a workflow, an e-book, a Line official account, a CNPG one-page guideline, and video materials. The evaluation of the model’s effectiveness demonstrated a significant increase in the caregivers’ mean knowledge and skill scores (p<.001) after implementation. The caregivers and professional nurses reported the highest level of satisfaction with the nursing service model. The complication rate was 2.5%, and hospitalization costs were significantly lower (p<.001), with an average reduction of 2,616.09 THB per patient.